VILLAGE FUNDS, BUSINESS MODEL PREFERENCE, PARTICIPATORY APPROACH AND ELITE CAPTURE IN TWO VILLAGE-OWNED ENTERPRISES IN BOGOR REGENCY - Andykha David Novri Sitanggang; Akhmad Solikin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
One manifestation of village community empowerment is the establishment of village-owned enterprises (Badan Usaha Milik Desa, BUMDesa). This study seeks to illustrate whether village funds dominate capital structure, how village head and villagers select business preferences, and whether elite capture phenomena probably occur in two BUMDesa in Bogor Regency. The results of the study show that village funds and government funding still remain the main source of BUMDesa's capital. In the selection of business sectors, one BUMDesa has adhered to a participatory principle while other BUMDesa still depends on the initiative of the village bureaucrats. The elite capture phenomenon possibly occurred at the implementation stage in one BUMDesa, as well as the planning stage at the other BUMDesa There has been no indication of elite capture in reporting and accountability aspect of these two BUMDesa.